Long-term trends and chemometric analysis of atmospheric air quality matrices in Nigeria (2003–2023) using NASA GIOVANNI satellite data - Daniel Omeodisemi Omokpariola; John Kanayochukwu Nduka; Martin Osita Anagboso; Patrick Leonard Omokpariola (Discover Applied Sciences)
Abstract Long-term trends and chemometric analysis of various atmospheric parameters in Nigeria from 2003 to 2023 using data from NASA satellites (Ozone Monitoring Instrument., OMI and Atmospheric Infrared Sounder, AIRS were investigated to provide insight into the spatiotemporal variations of surface temperatures, relative humidity and concentrations of pollutants such as nitrogen dioxide (NO₂), sulphur dioxide (SO₂), carbon monoxide (CO), carbon dioxide (CO₂), methane (CH₄), formaldehyde (HCHO), and ozone (O₃). Data was collected and analyzed using the NASA GIOVANNI platform, a web-based tool providing access to Earth science data. Statistical analysis including mean, range, standard error of the mean (SEM), variance, coefficient of variance, standard deviation, median, skewness, kurtosis, regression plot, correlation, Pearson Correlation, Dendrogram Clustering, and Scatter Plot were conducted to determine the trends and relationships between atmospheric parameters. Results indicate significant fluctuations and trends in all the atmospheric parameters over the study period, NO₂ levels exhibited undulating fluctuations with peaks in certain years; similarly, formaldehyde concentrations demonstrated variations attributed to volatile organic compounds (VOCs) from industrial processes and vehicular emissions. The study showed increasing trends in CO₂ concentrations, indicative of anthropogenic contributions to the greenhouse effect and climate change. Chemometric and statistical analysis, including scatter plots, dendrogram clustering, and Pearson correlation, revealed complex relationships between atmospheric parameters, suggesting common pollution sources and interactions. Positive correlations between certain pollutants imply shared influences and chemical reactions, while negative correlations suggest dissimilar pollution sources and atmospheric dynamics. This study with implications for regional climate and air quality management strategies is aimed at a better understanding of atmospheric dynamics and air quality in Nigeria, offering valuable insights for environmental monitoring, policy-making, and public health initiatives.